2013
DOI: 10.1177/230949901302100113
|View full text |Cite
|
Sign up to set email alerts
|

The Endolog System for Moderate-to-Severe Hallux Valgus

Abstract: The Endolog system achieved good outcome for moderate-to-severe hallux valgus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
3
13
1
Order By: Relevance
“…Reduction problems or recurrence can also be seen due to fixation complications (6,16,22). The application of an ILP has some advantages over other methods, in terms of union, stability, and recovery time, as well as the complication rates, which are more likely to be reduced (23). In our study this fixation method showed not only radiological, but also clinical improvement.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Reduction problems or recurrence can also be seen due to fixation complications (6,16,22). The application of an ILP has some advantages over other methods, in terms of union, stability, and recovery time, as well as the complication rates, which are more likely to be reduced (23). In our study this fixation method showed not only radiological, but also clinical improvement.…”
Section: Resultssupporting
confidence: 52%
“…ILP provides strong fixation on osteotomy site, early bone bridging and weight-bearing. Compared to other endolog implants, the main disadvantage is that the locking screws, which are inserted into the metatarsal cottage in osteoporotic patients, can create fissures in the cortex, but this can be prevented with cerclage wires (23). This complication developed in 2 patients of the current study but they had no complaints of discomfort or unstable fixation.…”
Section: Resultsmentioning
confidence: 66%
“…Multiple retrospective studies have reported the results of many different techniques proposed for HV correction, but, to the best of our knowledge, this is the first prospective study reporting the outcome of the Endolog technique at the 4 year follow-up. Only one retrospective study [ 22 ] showing midterm outcome of this device has been published.…”
Section: Discussionmentioning
confidence: 99%
“…The most important finding of the study was that the MI LR of the first MTP joint was a safe and reliable technique that was performed in cadavers without damaging any neurovascular structures or articular cartilage. Both the PATR and EPLR techniques aimed to release the adductor tendon, and they were successful in doing so without a significant Carvalho et al, 7 Martínez Nova et al, 30 Kurashige et al 22 Adductor hallucis tendon Biz et al, 4 Díaz Fernández, 15 Martinez Nova et al, 31 Cervi et al, 8 Pichierri et al 34 Adductor hallucis tendon and partial lateral capsule Scala et al 35 Phalangeal head of adductor tendon and adherences between lateral sesamoid and plantar side of the capsule De Lavigne et al 12 Adductor tendon, plantar capsule, and transverse metatarsal ligament Lee et al 23 Lateral part of the plantar plate and lateral phalangeal-sesamoid ligament Gicquel et al 18 Lateral phalangeal-sesamoid ligament and both medial and lateral suspensory ligaments Jowett et al 21 Lateral phalangeal-sesamoid ligament Lucas et al, 26 Crespo Romero et al, 10 Siclari et al, 37 Brogan et al 6 Not specified during technique description Bauer et al, 2,3 Di Giorgio et al 16 "Abductor" tendon transverse head and capsule difference (P = .85). The PATR was successful in achieving a complete release of the tendon, whereas the EPLR achieved a three-fourths release in most of the cases.…”
Section: Discussionmentioning
confidence: 99%